(untitled) (Asian Journal of Medical and Biological Research, 2018)
The purpose of this study was to comparative histomorphological investigation of the non affected and affected bile duct and gall bladder by fascioliasis in Black Bengal goat. The average weight of affected gall bladder was 26.10±0.70 gm which was significantly (p<0.001) higher than non affected gall bladder (19.40±0.96 gm). The average length and girth of affected gall bladder were 10.30±0.37 cm and 8.24±0.30 cm, respectively which were also significantly (p<0.001) higher than the length (6.10±0.30 cm) and Girth (5.85±0.25 cm) of non-affected gall bladder of Black Bengal Goat. The gross changes in acute form, thickening of the bile ducts and fibrosis in a portal area due to chronic fascioliasis was found in case of affected bile duct but were not found in case of non affected liver. A brownish exudates and a number of mature Fasciola gigantica were found in the lumen. The adult Fasciola gigantica was noticed in cross section in the lumen of the thickened bile ducts. Acute pathological lesions could only be produced by developing flukes prior to their entry to the bile ducts. Microscopically the epithelial layer of the bile ducts were seen to the partially disintegrated, but simultaneous proliferation of epithelial cells occurred. Thickening of the bile ducts was the result of connective tissue proliferation. Deposition of bile pigment in the tissue space and bile duct in some parts showed periductal cellular infiltrations, mainly neutrophiles, lymphocyte and eosinophiles. No calcification in the wall of the bile ducts in chronic Fascioliasis in goat could be seen in this study. The gall bladder was very dark usually contained blood clots, the consistency of bile was also very dense. Microcopically hyperplasia of the tubuloalveolar glands and numerous eggs were seen in the bile of infected goat which were absence in case of non infected goat. Asian J. Med. Biol. Res. December 2018, 4(4): 406-415